Impact of Inclement Weather on Overwinter Mortality of Montezuma Quail in Southeast Arizona - Pedro M. Chavarria; Angel Montoya; Nova J. Silvy; Roel R. Lopez (National Quail Symposium Proceedings, 2017)
Inclement weather such as droughts or hard freezes are known to negatively impact quail species and population viability models exist which have evaluated northern bobwhite (Colinus virginianus) response to summer and winter catastrophes. Previous research suggests inclement weather may be an important factor that contributes to mortality of Montezuma quail (Cyrtonyx montezumae), but few data have been collected to evaluate actual rates of overwinter mortality. We evaluated the overwinter mortality of Montezuma quail in southeast Arizona following an episode of severe winter weather consisting of 27.54 cm of precipitation, which occurred from January to March 2010. Overwinter mortality for radio-marked birds (n 1⁄4 23) was 95.6%. Total abundance using flush counts at a control site estimated an 88% reduction in the population following the episode of above-average precipitation. Post-hunting season flush counts across multiple study sites throughout the Coronado National Forest also support this trend. The 3-year (2007–2009) average (6 SD) (41.67 6 4.73) of birds flushed was 80% higher than number of birds (n 1⁄4 8) flushed in the 2010 post-hunting season.
Keywords: Appleton-Whittell Research Ranch; Coronado National Forest; covey size; Cyrtonyx montezumae; dog surveys; flush counts; freezing; Mearn’s quail; Montezuma quail; National Audubon Society; overwinter mortality; precipitation; radiotelemetry